Kegiatan Kokurikuler Mendukung Pendalaman Materi Siswa di SMA Negeri 1 Jakenan - Amida, Ale Sandya Rindi; Alfiah, Alfiah (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
Co-curricular activities are activities carried out outside curricular and extracurricular hours. This study aims to discover that co-curricular activities support the deepening of student material. The method used in this study is a qualitative method of experimentation. The data in this study collected data using field experiments. As for data management using content analysis. In this study, the author found four co-curricular activities that can support the deepening of student material: MOPDB (NewStudent Orientation Period), GLS (School Literacy Movement), Adiwiyata School, and Study Tour. These activities have been proven to support the deepening of student material inside and outside the student subject matter and foster good character for students.